Development of functionalized CuO nanoparticles for enhancing the adsorption of methylene blue dye. Issue 1 (1st January 2020) - Geetha, M. P.; Pratheeksha, P.; Subrahmanya, Bhat K.
Abstract: Water pollution by dyes from industries is a serious environmental problem. The toxicity of dyes constitutes a great risk to the environment and human health. Due to the simplicity and cost-effectiveness of the remediation process, adsorption has been widely accepted in wastewater treatment. Recent advances in nanotechnology offer considerable advantages in wastewater treatment via the introduction of porous nanomaterials, namely, metal oxide nanoparticles, carbon nanomaterials, and nanocomposites as adsorbents. In this study, a comparison is done between the functionalised and bare nanoparticles in enhancing the adsorption activity of chitosan in adsorbing methylene blue dye. Functionalized CuO nanoparticles were synthesized and characterized by FTIR, Powder X-ray Diffraction (XRD), SEM, and XPS methods. The crystallite size of CuO particles was found to be ~10 nm. The CuO nanoparticle was then functionalized to produce CuO-EDTA and CuO-EDTA-Silane complexes. The development of such functionalized nanoparticles leads to multi-functional properties such as the ability as catalysts in the presence of sunlight for degradation of dyes as well as adsorption of dyes. The BET adsorption study of the functionalized nanoparticles revealed it has a higher surface area than the pure CuO nanoparticles. These bare and functionalised nanoparticles were then separately dispersed with chitosan and adsorption study was done separately. The functionalised nanoparticles with chitosan shows more adsorption activity.